Evaluation of the quality of online information about perinatal depression in China - Li, Miaomiao; Wan Abas, Wan Anita; Ma’rof, Aini Azeqa; Wang, Peng; Wang, Xiaoyan (Redfame Publishing Inc., 2024)
This study assessed the quality of Chinese-language websites that provide information about perinatal depression, focusing on their compliance with recognized quality standards, the impact of information content providers on information quality, and the correlation between search engine ranking and quality. We conducted a systematic search on the Baidu search engine and screened 55 relevant websites. The quality of these websites was assessed using the DISCERN instruments. Our findings suggest that the quality of information on websites about perinatal depression is predominantly 'poor', with commercial sites constituting the entirety of the sample, although health information content provided by non-profit organizations demonstrating significantly higher quality. There was a significant negative correlation between search engine rankings and the quality of information on perinatal depression, suggesting that higher quality content is less likely to be searched for and may hinder access to reliable information. This study highlights the urgent need for mechanisms to prioritize the display of high-quality information in search engine results to provide better assistance to Chinese patients with perinatal depression.